Pengaruh Laju Injeksi Karbondioksida terhadap Oksigen Terlarut dan Pertumbuhan Spirulina platensis - Al Anshori, Aziz; Sri Ngabekti; Andhina Putri Heriyanti; Amnan Haris (Universitas Negeri Semarang, 2024)
Indonesia has a high and continually increasing total greenhouse gas emission. Carbon dioxide absorption can be mitigated by utilizing the photosynthesis process of microalgae. Spirulina platensis was chosen as the sample to be cultivated in this study due to its ease of cultivation and its status as a large-scale carbon dioxide absorber. The objective of this research is to analyze the effect of varying carbon dioxide injection rates on dissolved oxygen and the growth of S. platensis. This research employed an experimental method involving semi-mass cultivation using a 12 L volume tube photobioreactor (PBR) as a container with three treatment variations. These variations included culture P0 (without injection/control), culture PA (0.5 L/minute), and culture PB (1 L/minute). The data analysis revealed that the variation with an increase in dissolved oxygen levels and enhanced growth of S. platensis was most optimal in culture PB (1 L/min). One-way ANOVA results showed significant differences between culture P0 (without injection) and classified data indicating that culture PB (1 L/min) fell into a high-level classification. The average dissolved oxygen value for culture PB (1 L/min) was 7.9 mg/L, with a cell density average of 0.651 cells/ml and a dry biomass weight of 3.8 grams. The conclusion drawn is that varying carbon dioxide injection rates significantly affect dissolved oxygen levels and the growth of S. platensis, as evidenced by cell density and biomass calculations. The effect on the S. platensis culture is a notable increase in both parameters. The application of varying carbon dioxide injection rates in the cultivation of S. platensis may serve as a reference for identifying the optimal carbon dioxide injection rate during semi-mass cultivation.